2022
DOI: 10.1186/s13045-022-01381-6
|View full text |Cite
|
Sign up to set email alerts
|

JMJD4-demethylated RIG-I prevents hepatic steatosis and carcinogenesis

Abstract: Background Hepatocarcinogenesis is driven by necroinflammation or metabolic disorders, and the underlying mechanisms remain largely elusive. We previously found that retinoic acid-inducible gene-I (RIG-I), a sensor for recognizing RNA virus in innate immune cells, is mainly expressed by parenchymal hepatocytes in the liver. However, its roles in hepatocarcinogenesis are unknown, which is intensively investigated in this study. Methods DEN-induced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…As described previously, mouse livers were digested to obtain single-cell suspensions A [ 20 ]. Dissociated single cells were stained with AO/PI for viability assessment using a Countstar Fluorescence Cell Analyzer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously, mouse livers were digested to obtain single-cell suspensions A [ 20 ]. Dissociated single cells were stained with AO/PI for viability assessment using a Countstar Fluorescence Cell Analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…DHX58 is regarded as a non-canonical RNA-binding protein (RBP) due to its ability to associate with RNAs [ 19 ]. We previously focused on the roles of DDX/DHX family members, including DDX58 and DDX46, in regulating liver physiopathology and inflammation [ 20 22 ]. However, the potential roles of DDX/DHX family members in the development of hepatic ferroptosis remain unknown up to now.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that JMJD4 demethylates retinoic acid-inducible gene-I to prevent necroinflammation and NASH (non-alcoholic steatohepatitis)-induced hepatocarcinogenesis. 66 In this context, it is relevant to note that abnormal αKG anabolism can generate oncometabolites: isocitrate dehydrogenase 1 and 2 (IDH1/2) are enzymes that normally catalyse the interconversion of isocitrate and αKG. IDH1/2 are frequently mutated in cancers, but not in HCC, and the gain-of-function IDH1/2-mutantenzymes lead to the accumulation of the oncometabolite D-2-hydroxyglutarate, resulting in aberrant DNA and histone methylation by competitively inhibiting enzymes such as TET and JMJD.…”
Section: Glutamine Consumption In Cancermentioning
confidence: 99%
“…Habtemariam et al also revealed that eriodictyol showed neuroprotective effects and alleviated oxidative stress via activating nuclear factor erythroid 2‐related factor 2 (Nrf2)/heme oxygenase‐1 (HO‐1) axis. [ 15 ] Interestingly, Nrf2/HO‐1/NQO1 signaling pathway is also found to be involved in the development of different cancers, such as thyroid cancer, [ 16 ] prostate cancer, [ 17 ] cervical cancer, [ 18 ] and so on. Besides, the inhibiting effect of eriodictyol on tumor was also reported.…”
Section: Introductionmentioning
confidence: 99%